Fabrication of tapered fiber based ring resonator - Harun, Sulaiman Wadi; Lim, K.S.; Jasim, A.A.; Ahmad, Harith (IOP Publishing, 2010)
Tapered fiber based ring resonators are fabricated and its optical characteristic is investigated in detail. The ring resonator is fabricated by coiling the tapered fiber, which is firstly made by heating and stretching a piece of optical fiber, after the polymer protective cladding has been removed The comb filter with a constant free spectral range (FSR) and the maximum extinction ratio of 4.2 dB is achieved by a single-mode fiber based ring resonator. The FSR of ring resonator can be adjusted by controlling the diameter of the ring. The extinction ratio is improved in the polarization maintaining fiber based ring resonator where the maximum extinction ratio of 14 dB is achieved at 1531 nm region.